Development of models of spatial analysis of status of interactive processes of complex systems - Tvoroshenko, I. (Publishing House “Baltija Publishing”, 2019)
Given that objects of special purpose function in a priori uncertainty, characterized by a fuzzy space of states, which requires new intellectual approaches to increase the reliability of the decisions that are adopted, characterized by functional and territorial distribution, a complex hierarchy of interacting processes. It is necessary to predict certain requirements to the mathematical apparatus, methods of objectoriented modeling and analysis of interacting processes of a complex system.
Keywords: Development of models; spatial analysis; interactive processes; complex systems